因式分解:6x^3-11x^2+x+4
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:57:19
因式分解:6x^3-11x^2+x+4因式分解:6x^3-11x^2+x+4因式分解:6x^3-11x^2+x+46x^3-11x^2+x+4=6x^3-6x^2-5x^2+5x-4x+4=6x^2(
因式分解:6x^3-11x^2+x+4
因式分解:6x^3-11x^2+x+4
因式分解:6x^3-11x^2+x+4
6x^3-11x^2+x+4
=6x^3-6x^2-5x^2+5x-4x+4
=6x^2(x-1)-5x(x-1)-4(x-1)
=(x-1)(6x^2-5x-4)
=(x-1)(2x+1)(3x-4)
6x^3-11x^2+x+4
=(2x+1)(3x-4)(x-1)
因式分解:6x^3-11x^2+x+4
因式分解:6x^3-11x^2+x+4
因式分解:x^4+x^3+3x^2+x+6
6x^2+11x+4因式分解
因式分解3x^2-11x+6
因式分解6x^2-11x+3
因式分解(x-3)(x+2)+6x
因式分解x^3+6x^2+11x+6
将x^3-6x^2+11x-6 因式分解
因式分解:x 3 + 6 x 2 + 11 x + 6
因式分解2x^3-x^2+11x+6如题快
2x*3+11x*2+17x+6因式分解
x^3-16x^2+11x-6因式分解
x^3+x^2+11x+6因式分解
因式分解x^3-4x^2-11x+30
3x^3+6x^2+4x+8 因式分解
因式分解x'3-4x'2+6x-3
2x^3+4x^2-6x 因式分解